Practical Validation of the ICAP Theory in China: Holistic Module Learning in the Shandong 271 Education Group - Meng, Weijie; Zhao, Fengping; Zhou, Longjun (Science Insights Education Frontiers, 2023)
ICAP is one of the most impactful theories in the international community of cognitive and learning science. ICAP research focuses on active learning and student engagement with high applicability and guiding value. In the context of the reform of curricula and instruction in China, this article seeks to pinpoint the commonalities between the ICAP theory and the rationale underlying the holistic module learning model prevalent in schools at Shandong 217 Education Group to verify the practicality of applying the theory to Chinese education.